Neuroendocrine regulation of animal vocalization : mechanisms and anthropogenic factors in animal communication - Rosenfeld, Cheryl S.; Hoffmann, Frauke (Academic Press, 2021)
Neuroendocrine Regulation of Animal Vocalization: Mechanisms and Anthropogenic Factors in Animal Communication examines the underpinning neuroendocrine (NE) mechanisms that drive animal communication across taxa. Written by international subject experts, the book focuses on the importance of animal communication in survival and reproduction at an individual and species level, and the impact that increased production and accumulation of endocrine-disrupting chemicals (EDCs) can have on these regulatory processes. This book discusses sound production, perception, processing, and response across a range of animals. This includes insects, fish, bats, birds, nonhuman primates, infant humans, and many others. Some chapters analyze how neuroactive substances, endocrine control, and chemical pollution affect the physiology of the animal's perceptive and sound-producing organs, as well as their auditory and vocal receptors and pathways. Other chapters address the recent approaches governments have taken to protect against the endocrine disruption of animal (vocal) behaviors. The book is a valuable resource for researchers and advanced students seeking first-rate material on neuroendocrinological effects on animal behavior and communication.